Histidine-based copper tetrapeptides as enantioselective catalysts for aldol reactions - Begum, Sharifa Zaithun; Abdul Malek, Emilia; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne; Abdul Rahman, Mohd Basyaruddin (Royal Society of Chemistry, 2018)
Copper(II)-peptides are widely used as industrial catalysts such as in the aerobic oxidation of organic molecules, formation of new C–H bonds and in the azide–alkyne cycloaddition reaction. The length of peptides and the effect of adding copper metal into peptides were questioned in their field of applications. Five novel histidine-based tetrapeptides with the sequences HAAD (P1), HAFD (P2), HAVD (P3), AGHD (P4) and PGHD (P5) were synthesized using the solid phase peptide scheme and analysed with high performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC-MS) with percentage purities as high as 99.5%. All the peptides were positively charged (+1) and the molecular weight calculated from m/z values of MS results coincided with the theoretical molecular weight of the peptides. Copper(II)-peptides derived from these peptides and copper(II) acetate monohydrate (CuP1–CuP5) in a 1 : 2 ratio was synthesised, purified and characterised by ultraviolet-visible spectroscopy (UV-Vis), ultraviolet-fluorescence spectroscopy (fluorescence) and fourier transform infrared spectroscopy (FTIR), circular dichroism spectroscopy (CD) and optical rotation polarimetry. It provided the necessary information on the secondary structure and the successful binding of copper(II) to the specific amino acids, hence leading to the putative geometry of copper(II)-peptides and the difference in the chirality of amino acids, peptides and copper(II)-peptides. The catalytic activities of the synthesised complexes were evaluated. CuP1 & CuP3 catalysed both the asymmetric aldol reactions with high enantioselectivity of p-nitrobenzaldehyde with cyclohexanone (% ee = 87.3 & 80.3, respectively) and of p-anisaldehyde with cyclohexanone (% ee = 95.5 & 90.9, respectively).